Know how to regrow—axon regeneration in the Zebrafish spinal cord - Tsata, Vasiliki; Wehner, Daniel (Cells, 2021)
The capacity for long-distance axon regeneration and functional recovery after spinal cord injury is poor in mammals but remarkable in some vertebrates, including fish and salamanders. The cellular and molecular basis of this interspecies difference is beginning to emerge. This includes the identification of target cells that react to the injury and the cues directing their pro-regenerative responses. Among existing models of successful spinal cord regeneration, the zebrafish is arguably the most understood at a mechanistic level to date. Here, we review the spinal cord injury paradigms used in zebrafish, and summarize the breadth of neuron-intrinsic and-extrinsic factors that have been identified to play pivotal roles in the ability of zebrafish to regenerate central nervous system axons and recover function.
CRIS-Team Scopus Importer:2022-08-03
Keywords: Axon regeneration; Functional recovery; Spinal cord injury; Zebrafish